Caracterización biogeográfica de la Provincia Castellano-Maestrazgo-Manchega en Andalucía - Navarro Reyes, Francisco B.; Jiménez Morales, María N.; Lorite Moreno, Juan; Valle Tendero, Francisco (Lazaroa, 2001)
In this study we delineate new biogeographical boundaries for the Castilla-Maestrazgo-Mancha province in Andalusia (North of Granada and Almería) by means of a pattern of study based on the cluster analysis of 49 phytosociological relevés distributed in 3 sintaxa chosen as biogeographical discriminants, all belonging to the class Rosmarinetea officinalis.